Corrosion and tribocorrosion mitigation of perhydropolysilazane-derived coatings on low carbon steel. (December 2020) - Yang, Ni; Wang, Wenbo; Cai, Wenjun; Lu, Kathy
Highlights: Highly protective SiON-based coatings were synthesized on low carbon steel under various temperatures. The coating- substrate adhesion strength was maximum at 200 °C pyrolysis temperature. The coating derived under 600 °C offered the best corrosion and tribocorrosion protection. Abstract: Perhydropolysilazane (PHPS) is a polymer with [–SiH2 –NH–]n repeating units. By pyrolysis with PHPS as a precursor, highly adhesive and protective silicon oxynitride (SiON)-based coatings were synthesized. The formation of SiOSi bonds increased with pyrolysis temperature. Both the hardness and Young's modulus of the PHPS-derived coatings were enhanced at higher pyrolysis temperatures. The PHPS-derived coatings significantly enhanced the corrosion resistance of low carbon steel in a 0.6 M NaCl aqueous solution, especially for the coatings with the formation of extensive Si-O-Si bonds. The PHPS-derived coating at the pyrolysis temperature of 600 °C exhibited the best resistance to corrosion and tribocorrosion.